Impacted maxillary canines and their relationship with lateral incisor resorption: a cone beam computed tomography (CBCT) study - Yilmaz Hakan; Ozlu Fethiye Cakmak; Icen Murat; Icen Erdi (Sciendo, 2020)
The spatial position of a canine can affect the level of proximal root resorption and the success of orthodontic treatment. The aim of this study was to examine the mesiodistal and vertical position of impacted maxillary canines and to assess their relationship with the lateral incisor by using cone beam computed tomography (CBCT).